Design and Build A Land Conflict Management Model - Samosir, Agustin Iterson; Mulyanto, Budi; Achsani, Noer Azam; Suroso, Arif Imam (International Journal of Accounting and Economics Studies, 2026)
Land conflicts in Indonesia persist at a high level due to overlapping claims, inadequate ‎historical documentation, and discrepancies in authority between institutions. This study aims to ‎analyze the governance of conflict resolution by ATR/BPN, map the regulatory-implementation ‎relationship, and design a data-based non-litigation conflict management model. The study was ‎conducted in Jambi Province to examine the case of PT Kaswari Unggul, ‎PT DAS, PT FPIL, PT EWF, and the TORA process in Muaro Jambi. Data were collected ‎through interviews, FGDs, observations, and document reviews; analysis using regulatory ‎mapping, Soft System Methodology, and Analytical Hierarchy Process for strategy prioritization. ‎The results indicate that the root of the main problem lies in poor subject–object verification and ‎limited data integration. The merging of DUKCAPIL data for subjects and RTRW/administrative ‎boundaries for objects accelerates clarification, reduces social friction, and enables settlement ‎options such as enclaves, 20% partnership grants, and benefit-sharing schemes. The proposed ‎model emphasizes five factors: data accuracy, process effectiveness, justice/recognition of ‎rights, community participation, and institutional integration; and involves ATR/BPN, ‎DUKCAPIL, communities/customs, NGOs, and academics. In conclusion, the national ‎standardization of DUKCAPIL-RTRW verification, the establishment of independent mediation ‎units with cross-access to data, and institutional interoperability are crucial to accelerate ‎equitable resolution and reduce the recurrence of conflicts. Cross-provincial trials are suggested ‎to measure the impact on duration, cost, post-agreement compliance, public trust, and ‎sustainability of spatial planning, as well as the effectiveness of ongoing multi-stakeholder ‎coordination‎.